Incorporating Memes and Instagram to Enhance Studentâs Participation - Purnama, Agnes Dian (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
Todayâs teaching and learning faces more challenges as technology keeps on updating itself. Teachers are expected to adopt as many as possible technology products to promote studentsâ engagement in classroom activity. Utilizing technology products may help teachers to decrease studentsâ boredom inside classroom since it proposes a new kind of activity. The main purpose is to create an enjoyable teaching and learning environment as well as to trigger students to be creative. By highlighting youthsâ characteristics that tend to be visual and addicted to rapid information, memes and Instagram may be used as one of the strategies to develop an innovative teaching and learning process.DOI:Â https://doi.org/10.24071/llt.2017.200101